ANALISIS TINGKAT PENGETAHUAN PASIEN DI APOTEK MANFAAT TERHADAP PENGGUNAAN AMOXICILIN - Erlina Azahari; Tata Perwata (Jurnal Farmaku (Farmasi Muhammadiyah Kuningan), 2018)
This study was conducted with the aim to know the level of knowledge of patients in the pharmacy benefits to the use of Amoxicillin. This research uses purposive sampling technique. The data were collected by questionnaire. The questionnaire used was a closed questionnaire in patients prescribing amoxicillin. Data analysis technique used is using percentage formula. Data collected data can be concluded that the level of knowledge of patients in the pharmacy benefits to the use of amoxicillin categorized quite well with an average yield of 66.85%.